Anti-tyrosinase Activity of 3’,4’,5’-Trimethoxychalcones: Experimental and Computational Studies - Danova, Ade; Hermawati, Elvira; Chavasiri, Warinthorn; Mujahidin, Didin; Musthapa, Iqbal; Kurniadewi, Fera (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Tyrosinase inhibitors are utilized as preservatives in the food industry and skin-lightening agents in the medical and cosmetic sectors. However, there has been little progress in clinical trials owing to challenges such as low bioavailability, significant skin irritation, and instability. Hence, the objective of this study was to evaluate the inhibitory activity of 3’,4’,5’-trimethoxychalcones through in vitro, molecular docking and molecular dynamics studies targeting tyrosinase. Five 3’,4’,5’-trimethoxychalcones (1-5) were evaluated their biological activity against tyrosinase for the first time. Compounds 4 and 5 were excellent inhibitory activity against tyrosinase with IC50 values of 1.9 and 1.7 μm compared with kojic acid and ascorbic acid. Isovanillin and catechol moieties are vital in this present study. This result was supported with molecular docking by shaping interaction in the catalytic site with histidine residues and the stability evaluation of the inhibitor-protein complexes using molecular dynamics simulation. The lipinski’s rules showed a fit with two potential inhibitors (4, 5). Therefore, 3’,4’,5’-trimethoxychalcones possessing isovanillin and catechol parts in the B ring are promising candidate for further study as tyrosinase inhibitors by evaluating their efficacy in vitro and in vivo.